Impacts of land use change on habitat quality and its driving mechanisms in the lake basin of Central Yunnan - Lanlan Qi; Meng Lu; Misbah Uddin; Min Wang; Jinghua Su; Xiaole Zhang; Jingxin Huang; Jinming Hu (Scientific Reports)
Abstract The five major plateau lake basins in central Yunnan are densely populated areas with high land use intensity. The spatiotemporal changes in land use significantly affect the ecological environment quality of the entire basin. This research utilized land use data from 1990 to 2020, and the InVEST model to analyze land use change and its impact on habitat quality in the basin. The results indicated that cropland has been the predominant land use type during this period but has steadily decreased, while the areas of forest land and impervious surfaces increased. Additionally, the intensity of conversion between different land types was significant, primarily involving the transformation of cropland into other land types. The overall habitat quality improved, predominantly characterized by high and relatively low grades of habitat quality. Regions experiencing improved habitat quality outnumber those degradation, and the spatial distribution of habitat quality showed "high at the edges, low in the lakeside areas" around each lake. Land use change was the most dominant factor influencing the distribution of habitat quality within the lake basin, with 91.89% of the contribution rate to habitat quality improvement attributed to transitions from cropland to forest and grassland, while 94.12% of the contribution rate to habitat quality degradation was due to the expansion of impervious surfaces and the encroachment of cropland into other ecological land uses. Therefore, the findings of this study provide important reference for future land use planning and ecological environmental protection in the lake basin of central Yunnan.